Media Pembelajaran Interaktif Pendekatan Etnomatematika Budaya Jawa Terhadap Hasil Belajar Siswa Materi Geometri: Penelitian - Isna Nur Aini; Martyana Prihaswati; Iswahyudi Joko Suprayitno (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to identify and examine the types of interactive learning media based on ethnomathematics that incorporate Javanese culture and their influence on students' learning outcomes in geometry. The research method used is the Systematic Literature Review (SLR), which includes formulating research questions, searching literature, setting inclusion and exclusion criteria, selecting relevant literature, presenting data, and drawing conclusions. The articles analyzed were sourced from Google Scholar within the 2020–2025 timeframe, resulting in 21 articles that met the inclusion criteria. The findings indicate that the dominant interactive media used include e-modules, application-based media, and digital animations. Javanese cultural elements commonly integrated into the learning media include the Joglo traditional house, Surya Majapahit batik, Kudus Tower, Grebeg Maulud ceremony, Sesaji Rewanda tradition, and traditional dances such as Tari Remo. These cultural elements are utilized to explain geometric concepts such as three-dimensional shapes, two-dimensional figures, geometric transformations, and coordinate systems. The use of interactive media based on local culture has been proven to significantly enhance students' conceptual understanding and learning motivation.